Fundamental Differences between Party Member Groups: the “Consolidation” in the Study of the Movements of the Communist Party of Thailand - srimanta, pathomporn (King Prajadhipok’s Institute Journal, 2020)
This study about the Communist Party of Thailand (CPT) focuses on various groups of members or comrades: the party leaders, intellectuals, and the based comrades in order to identify and analyze “differences” between the based comrades and other groups of the comrades that cannot be presented in the same kind of “story”. This appears to be an ignored subject of study, especially in the case of the “based comrades” who are always ignored and assumed to be just a part of other groups’ explanation without being considered as a unique social group. Consequently, the historical study of the CPT is significantly deficient. This research focuses on historical facts by conducting documentary research and comparison, interviews with former CPT members, and participant observation in order to debunk the known principles or theories. This study found that the party leaders, the intellectuals, and the based comrades of the CPT are disparate in structure, background, attitudes, and paradigms. Moreover, the structure of the party is unequal and it violates the well-recognized principles or theories. For these reasons, these groups of comrades are so disparate that they cannot be.